SUBPOPULATIONS AND METABOLIC ACTIVITY OF BLOOD MONONUCLEAR CELLS IN METABOLIC SYNDROME - I. D. Bespalovа; N. V. Ryazantseva; V. V. Kalyuzhin; B. Yu. Murashev; I. A. Osikhov; Y. A. Medyantsev; D. S. Afanas’eva (Медицинская иммунология)
Aim of study: to examine the features of expression of CD-markers of blood mononuclear leukocytes and their functional activity in the metabolic syndrome. Conducted a cross-sectional (transverse) study of 76 patients with essential hypertension (EH) II stage (BP <180/110 mm Hg.) [10] in conjunction with the metabolic syndrome and 20 people, formed the control group. Along with a complete clinical, laboratory and instrumental examination taken in a specialized cardiological clinic was conducted determination of surface markers of lymphocytes CD4+, CD8+ and monocytes CD36+ and assessment of the level of spontaneous production of reactive oxygen blood mononuclear leukocytes. Found that in patients with the metabolic syndrome compared with the control group the proportion of CD4+ lymphocytes and the level of spontaneous ROS production by mononuclear leukocytes significantly higher. The positive correlated interconnection between these indicators and the number of CD36+ monocytes with the majority of clinical and metabolic markers of MS confirmes their participation in mechanism of immune inflammation and oxidative stress in this pathological process.